RI SK FACTOR OF BACTEREMI A I N CHI LDREN WI TH PNEUMONIA - Asih, Retno (Indonesian Journal of Tropical and Infectious Disease, 2011)
Background: Pneumonia is known as a frequent cause of morbidity and mortality among children in developing countries. In children,it caused predominantly by bacteria. Bacteremia has been associated with severity and mortalitas of pneumonia. Identify factors caused bacteremia important to prevent severity and mortalitas of pneumonia. Objective: The objective of this study was to identify risk factors of bacteremia in children with pneumonia. Methods: A retrospective study was conducted in children with pneumonia in Dr. Soetomo Surabaya Hospital from January 2007 to December 2008. Blood cultures be performed on all of this patients. Factors associated with bacteremia were identified following review of medical records include clinical features, laboratory , radiology and blood culture results. Results: Frequency of bacteremia was 8,2% (36 patients) of 438 children with pneumonia. Interval from onset of symptoms to hospital admission more than 5 days (22.69 CI 95%), severe malnourished (OR 9.05 CI 95%), anemia (OR 2.44 CI 95%), leucocyt counts less than 5000/mm3 and more than 20.000/mm3 (OR 2.41 CI 95%) and paO2 less than 80 mmHg (OR 4.25 CI 95%) were at increased risk of bacteremia in children with pneumonia. Conclusion: Risk factors bacteremia in children with pneumonia included age under 1 year, symptoms more than 5 days, severe malnourished ,anemia, leucosyt counts less than 5000/mmand more than 20.000/mm3 and paO2 less than 80 mmHg.